Scientific Management of Knowledge as a Resource in the Learning System of Security and Defence - Stojko Stojkov; Sevdalina Dimitrova; Rumen Marinov (Proceedings of the ENTRENOVA - ENTerprise REsearch InNOVAtion Conference, Split, Croatia, 6-8 September 2018, 2018)
The need to introduce scientific management and change management, while respecting the requirements for efficiency and transparency in the security industry, requires the corresponding responsibility to the obligations and adaptability to the changes in the security environment, to the risks and challenges. Building knowledge-based security is a demanding task but also a challenge for teams in science education organizations in the security sector. The goal of scientific research is to provide, based on the scientific, systematic and managerial approaches, a relatively complete theoretical concept of the need for strategic knowledge management in the security system that will allow our country to be a source rather than a consumer of security in the modern European family and the Euro-Atlantic community. Modern knowledge management in the security system implies creating prerequisites for its successful management rather than administering the limited resources in the system.
Keywords: H56; 330; security and defence; strategic management; security and defence management; knowledge management